Pengaruh TPT, PDRB, dan TPAK Terhadap Kemiskinan di Provinsi Sumatera Utara Periode 2002-2023 - Tia Handani; Joko Suharianto (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
Poverty is a crucial issue for a country. Overcoming poverty requires a comprehensive and sustainable approach that encompasses various sectors. This study aims to determine the effect of the Open Unemployment Rate (TPT), Gross Regional Domestic Product (PDRB), and Labor Force Participation Rate (TPAK) on the number of poor residents. The data analysis technique used in this research is OLS (Ordinary Least Squares), utilizing time series data on the Open Unemployment Rate (TPT), Regional Gross Domestic Product (PDRB), Labor Force Participation Rate (TPAK), and poverty from 2002-2023 in North Sumatra Province. The results of this study indicate that the Open Unemployment Rate (IPT) does not affect poverty, whereas the Gross Regional Domestic Product (PDRB) and the Labor Force Participation Rate (TPAK) have a negative and significant impact on poverty. Meanwhile, simultaneously, the Open Unemployment Rate (TPT), Regional Gross Domestic Product (PDRB), and Labor Force Participation Rate (TPAK) affect poverty in North Sumatra Province from 2002 to 2023.